PENGEMBANGAN PERANGKAT PEMBELAJARAN BERORIENTASI PENDEKATAN SAINTIFIK PADA MATERI PERTUMBUHAN DAN PERKEMBANGAN DI KELAS XII SMA - Natalina, Mariani Natalina Mariani; ', Falziah; ', Arnentis (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study aims to develop a biology learning materials that oriented to scientific approach on the growth and development topic for senior high school grade XII. The learning materials consists of lesson plan (RPP); students worksheet (LKS); assessment sheet that consist of written, attitude, performance, product, project, portfolio and self assessment; and interactive learning media. This research was conducted at Biology Education Program Faculty of Teacher Training and Education University of Riau and the tryout at SMAN 8 Pekanbaru on June to December 2014. Validation sheet was used as data collecting instrument. Validation sheet was filled by the internal and external validator and for each learning materials. Data were analyzed by descriptive statistics. The result of validation showed that the mean score for lesson plan was 3.6, students worksheet was 3.5, written assessment was 3.5, attitude assessment was 3.6, performance assessment was 3.6, product assessment was 3.5, project assessment was 3.4, self-assessment was 3.5, portfolio assessment was 3.4 and interactive learning media was 3.3. Further, the tryout carried out with using 3rd meeting worksheets and self-assessment questionnaire to 34 students of class XII IPA 2 SMAN 8 Pekanbaru. Based on the results, it can be concluded that this learning materials could implemented through a field-scale trials.Key words: growth and development, scientific approach, the biology of learning, development